Need of Combining Proton Pump Inhibitors with Prokinetics: A Prospective Observational Survey Conducted in India - Faruqui, Arif Ahmed (Journal of Medicine, 2018)
Background: Gastro esophageal reflux disease (GERD), a highly prevalent disorder has adverse impact on quality of life. An estimated 40% of GERD patients have incomplete response to standard PPI therapy. For these PPI refractory patients, doubling the PPI dose or switching to another PPI are pursued by the treating physicians that might not be optimal. Therefore, an appropriate second line treatment should focus on addition of gastro-prokinetic drugs that stimulates gastric motility. Materials & Methods: This was a prospective observational study conducted in 118 patients suffering from symptoms suggestive of GERD, at four centers in Indian National Capital region to assess the overlap between GERD and delayed gastric emptying and to predict the need for combination therapy of PPI with pro-kinetic drug using Frequency Scale for the Symptoms of GERD (FSSG) score. Results: The mean total FSSG score was 16.37 ± 7.50. From 118 patients, 98 (83.05%) met the criteria for GERD with FSSG total score more than eight. The mean reflux score was 7.43 ± 4.08, while the mean dysmotility score was 8.94 ± 4.83. GERD patients in this study have a high mean FSSG score, whereas dysmotility symptoms proved to be more dominant than acid reflux. Conclusion: Based on the findings of this study, combination therapy of PPI with prokinetics is recommended in subsets of patients with high FSSG score J MEDICINE JUL 2018; 19 (2) : 74-78